Evaluación de un modelo de degradación de baterías de Ion Litio para aplicaciones en vehículos eléctricos y microrredes - Toapanta Hurtado, Jeferson Francisco (2022)
The present research work shows the evaluation of a methodology that allows modeling the degradation of lithium ion batteries when they present erratic charge and discharge cycles, that is, when different ranges of charge states are used from real values, the model It is established based on parameters indicated by the manufacturer in its specification sheet and is focused on different case studies in the context of microgrids and electric vehicles. The method used is based on an empirical model that serves to describe the behavior of the battery during different charge and discharge cycles until the end of its useful life is evidenced. The presented model determines a fixed degradation assuming symmetrical states of charge, which in practice is not real, since the batteries are charged/discharged in different cycles of use. Then, an update of the initial degradation is carried out using scaling parameters and based on a model based on similarity, it is possible to find the real degradation of the battery for each cycle of erratic use.